Epidemiological and clinical characteristics of imported cases of COVID-19: a multicenter study - Jinjun Zhang; Shixiong Yang; Yi Xu; Xinyan Qin; Jialiang Liu; Jinjun Guo; Sijia Tian; Shaoping Wang; Kai Liao; Ying Zhang; Yu Ma; Yuguo Chen (BMC Infectious Diseases, 2021)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic continues to expand. Herein, we report the epidemiological and clinical features of 478 patients with confirmed COVID-19 from a multicenter study conducted in four cities in China excluding Wuhan. Methods A total of 478 patients transferred by emergency medical services to designated hospitals in four major cities in China (Beijing, Chongqing, Jinan, and Nanning) were enrolled. We compared the characteristics of imported and indigenous cases and calculated the frequencies of fatal, severe, mild, and asymptomatic disease. The results were used to generate a pyramid of COVID-19 severity. Results The mean age of patients with COVID-19 was 46.9 years and 49.8% were male. The most common symptoms at onset were fever (69.7%), cough (47.5%), fatigue (24.5%), dyspnea (8.4%), and headache (7.9%). Most cases (313, 65.5%) were indigenous, while 165 (34.5%) were imported. Imported cases dominated during the early stages of the pandemic, but decreased from 1 February 2020 as indigenous cases rose sharply. Compared with indigenous cases, imported cases differed significantly in terms of sex (P = 0.002), severity of disease (P = 0.006), occurrence of fever (P < 0.001), family clustering (P < 0.001), history of contact (P < 0.001), and primary outcome (P < 0.001). Conclusions Within the population studied, imported cases had distinct characteristics from those of indigenous cases, with lower fatality rates and higher discharge rates. New infections shifted from imported cases to local infection gradually, and overall infections have declined to a low level. We suggest that preventing import of cases and controlling spread within local areas can help prevent SARS-CoV-2 infection spread.